‘ASPIRE’ Strategies for Strengthening Adolescents’ Sexual and Reproductive Health Role Modelling - Dr. Tshiamo Nerville Ramalepa (‘ASPIRE’ Strategies for Strengthening Adolescents’ Sexual and Reproductive Health Role Modelling, 2025)
This book presents strategies for adolescents’ sexual and reproductive health role modelling developed using the Adapting Strategies for Promoting Implementation Research and Equity (ASPIRE) process, which focuses on adapting equity-explicit implementation strategies. To improve conceptual clarity and application, this book acknowledges the distinction between mentors, peers, and role models. However, in this context, peers and mentors are regarded as individuals involved in role modelling. Peers are similar in age or status and engage with one another and exchange experiences to influence one another. Mentors offer deliberate, ongoing advice and assistance, usually in a more mutually beneficial and structured relationship. Moreover, role models are frequently admired and whose actions, principles, or accomplishments provide examples for others to follow; these include peers and mentors. Adaptation of strategy and guidelines is an effective process in research that can be used to adjust existing methods, programmes, practices, strategies, or procedures to make them more suitable for use with a certain target demographic or within a specific context. This method was used to develop novel strategies for adolescents’ sexual and reproductive health role modelling because of the paucity of literature and research regarding role modelling in sexual and reproductive health. The adaptation of strategies was aided by the findings from a scoping review and the findings from an empirical study about adolescents’ sexual and reproductive health role modelling. The Three-step ASPIRE process for Adapting Equity-Explicit Implementation Strategies guided the adaptation process. The ASPIRE process aims at adapting strategies to explicitly consider their impact on disparities, gaps, and outcomes. This book recommends strategies that role models such as parents, teachers, health professionals, peers, media personalities and community members should be integrated into the promotion of adolescents’ sexual and reproductive health. Health professionals should engage parents and caregivers as sexual and reproductive health role models for adolescents. Encourage parents to have honest, nonjudgmental discussions with their children about relationships, sexual health, and reproductive rights. In addition to reducing misinformation among adolescents, this can promote trust. Encourage the use of peer role modelling through peer education programmes, social media campaigns and youth-driven projects. Using the ASPIRE process to create context-specific strategies, this book provides a thorough method for improving the sexual and reproductive health of adolescents through role modelling. These strategies give parents, peers, teachers, health professionals, and community members a useful framework for working together to create a fair, informed, and healthy environment for adolescents. Ultimately, this approach promotes inclusive and sustainable health outcomes by bridging the gap in the literature and practice about role modelling in adolescent sexual and reproductive health. Contribution: This book will introduce role modelling as an effective strategy to address adolescents’ sexual and reproductive health challenges. It initiates the development of policies and programmes that use role modelling as a tool to promote sexual and reproductive health among adolescents.